Informational Role of Stock Price Synchronicity: Evidence from an Emerging Market - Hamouda, Moataz (AUC Knowledge Fountain, 2015)
The informational role of price synchronicity, the degree of co-movement a stock has with the entire market, has been the subject of investigation in this research. More precisely, the lead-lag relationship between stocks which exhibit high price synchronicity (high R2) and low price synchronicity (low R2) was studied using a VAR model. In testing the hypothesis that high R2 stocks lead the low R2 stocks, all the listed stocks in Bombay Stock Exchange (BSE) from January 1999 to December 2012 were examined and portfolios of equally weighted and value weighted High R2 (HS) and Low R2 (LS) were formed. It was found that both the equally weighted and value weighted high R2 stocks lead the low R2 stocks and not vice versa. Additionally, it was found that the high R2 stocks lead the returns of the entire market.